2017
DOI: 10.12697/poa.2017.26.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the historical origin of Joseon mummies considering the structural similarities between the burial systems of Korean and Chinese dynasties

Abstract: Joseon mummies have proved to be excellent subjects for scientific research on the health and disease statuses of pre-modern Korean peoples. Despite its academic significance, the origins of the Hoegwakmyo tomb in which the Joseon mummy was discovered have not yet been entirely revealed. Meanwhile, over the past several decades, there have been some reports on mummies and cultural artifacts preserved very well in the tombs of several Chinese dynasties (especially Song, Yuan, Ming and Qing). Although the Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 11 publications
2
53
0
Order By: Relevance
“…In the Jujagare , the Hoegwakmyo tomb was recommended as the ideal Confucianist gentlemen's burial. The ruling class of the Joseon Dynasty assimilated this concept and the Hoegwakmyo tomb became their elective type of grave [ 5 , 43 ]. However, what has become also evident nowadays is that the Joseon people did not want their corpses to be mummified.…”
Section: Why Did the Korean Mummies Spontaneously Preserve?mentioning
confidence: 99%
See 4 more Smart Citations
“…In the Jujagare , the Hoegwakmyo tomb was recommended as the ideal Confucianist gentlemen's burial. The ruling class of the Joseon Dynasty assimilated this concept and the Hoegwakmyo tomb became their elective type of grave [ 5 , 43 ]. However, what has become also evident nowadays is that the Joseon people did not want their corpses to be mummified.…”
Section: Why Did the Korean Mummies Spontaneously Preserve?mentioning
confidence: 99%
“…Since there is a close relationship between the ancient Korean people and Confucianism, researchers hypothesized that similar tombs and mummies were present in China, the country where Confucianism originated [ 5 ]. Interestingly, Chinese archaeologists reported that some graves dating to the Song and Ming dynasties were completely sealed by a mixture of lime, yellow clay soil, sand, and sticky rice water.…”
Section: Mummies Of Sticky Rice Soup Sealed Tombs mentioning
confidence: 99%
See 3 more Smart Citations